Till death [videorecording (Blu-Ray)] - Fox, Megan, 1986-; Macken, Eoin C.; Mulvey, Callan, 1975-; Roth, Jack, 1984- (Screen Media Films, 2021)
After a romantic evening in their secluded lake house, Emma awakens handcuffed to her dead husband. Trapped and isolated in the dead of winter, she must fight off hired killers to escape her husband's twisted plan.